Drainage of infiltrated rainwater in wall assemblies: Test method, experimental quantification, and recommendations. (September 2022) - Van Linden, Stéphanie; Lacasse, Michael; Van Den Bossche, Nathan
Drainage reduces the amount of water able to infiltrate toward the interior of wall assemblies. However, a portion of the infiltrated water remains in the assembly after drainage has occurred. The degree to which this retained portion of water affects the durability of the wall assembly can be evaluated by means of hygrothermal simulations. However, the number of studies reporting information on the retention percentage that can be applied as input for hygrothermal simulations and on the drainage performance of wall assemblies is, in general, quite limited. Therefore, an experimental study was developed, to assess governing test methods to evaluate drainage characteristics and to quantify retention of water in wall test specimens having various cavity widths and incorporating different drainage materials. It was concluded that apart from the absolute amount of retained water, the lateral spreading of water in the cavity and the overall wetted area, should also be considered, thereby resulting in reporting the retained amount relative to the wetted area. The latter values provide more detailed information on the behavior of water in the cavity. Additionally, it was concluded that a clear cavity of 1 mm can drain water more efficiently than a cavity of 10 mm. As well, the surface texture of drainage materials affected the spreading and retention of water within the cavity and the use of a drainage mat in the cavity resulted in an increased relative retention but a reduced lateral spreading of the water.